Peramalan Tingkat Penghunian Kamar Hotel Menurut Klasifikasi Hotel Kota Surakarta Menggunakan Least Square Method - Wulandari, Septi (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2025)
Hotel Room Occupancy Rate is important for hotels to see how many rooms have been filled or sold, including in star and non-star hotels in Surakarta City. The increase in room occupancy in star and non-star hotels has an impact on the sustainability of these hotels' businesses. These hotels need to predict the Room Occupancy Rate every month. The purpose of this study is to forecast the hotel room occupancy rate according to the classification of star and non-star hotels in Surakarta city in 2024-2025. Forecasting is done by referring to the time series data of hotel room occupancy rates from January 2018 to December 2023. The method used for prediction is the Least Square Method (LSM). The results showed that the equation model obtained was y = 42,58 + 0,01t for the Room Occupancy Rate of Star and Non-Star Hotels in Surakarta City. The forecasting results of the equation model from January to December 2024-2025 show that the Hotel Room Occupancy Rate has increased. The results of this study can be the basis for star and non-star hotels in Surakarta City in the efficiency of hotel management, such as optimizing existing resources in the hotel, improving room services, marketing strategies for room sales, and improving the service of the hotel room reservation.